1997
DOI: 10.1111/j.1532-5415.1997.tb01479.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐Leg Balance Is an Important Predictor of Injurious Falls in Older Persons

Abstract: One-leg balance appears to be a significant and easy-to-administer predictor of injurious falls, but not of all falls. In our study, it was the strongest individual predictor. However, no single factor seems to be accurate enough to be relied on as a sole predictor of fall risk or fall injury risk because so many diverse factors are involved in falling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
470
0
23

Year Published

2000
2000
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 761 publications
(499 citation statements)
references
References 10 publications
6
470
0
23
Order By: Relevance
“…The decision was made to use 10 s to indicate successful unilateral balance because it is a time-efficient measure that can be performed in high-volume clinics. Five seconds has been suggested as a single leg stance time criterion standard, however this is noticeably lower than age matched controls (17.1-24.3), thus as a result a higher standard of 10 s was selected for the cut-off in the current study [40,41,33,42].…”
Section: Methodsmentioning
confidence: 99%
“…The decision was made to use 10 s to indicate successful unilateral balance because it is a time-efficient measure that can be performed in high-volume clinics. Five seconds has been suggested as a single leg stance time criterion standard, however this is noticeably lower than age matched controls (17.1-24.3), thus as a result a higher standard of 10 s was selected for the cut-off in the current study [40,41,33,42].…”
Section: Methodsmentioning
confidence: 99%
“…The ability to stand on a single leg is an important predictor of falls: One study demonstrated that the chance of sustaining an injury due to a fall is twice as high if one is unable to perform the OLS for 5 seconds. 62 Yoga standing poses that invoke the use of hip abductors and/or adductors, such as tree pose (vrksasana), mirror the biomechanical demands required to successfully execute the OLS. 63 Therefore, one may hypothesize that practicing poses that challenge static balance would lead to improvements in balance.…”
Section: Discussionmentioning
confidence: 99%
“…3 Balance was assessed using the Functional Reach 8 and One-Leg Balance Test. 22 Functional capacity was assessed by the Brazilian version of the Human Activity Profi le (HAP), which has items that are diffi cult enough to determine high levels of capacity or functional performance, thereby minimizing the ceiling effect commonly seen in other functional assessment scales by assessing the individual's functional level as well as the level of physical activity. 20 The World Health Organization Quality Of Lifebref (WHOQOL), 11 an abbreviated version of the WHOQOL-100, was used for the assessment of quality of life domains.…”
Section: Methodsmentioning
confidence: 99%